Evaluasi Biaya pada Pembangunan Gedung Auditorium Politeknik Ilmu Pelayaran Kota Makassar - Hamkas, Martin; Ashad, Hanafi; Bachmid, Sofyan (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The construction of the Maritime Science Polytechnic building in Makassar City (PIP), is based on the results of a planning review which consists of several activity components, namely; Preparation of work, Land, Structure, Architecture, Mechanical, Power House. With reference to the RAB, the Structure component constitutes the largest portion of the budget allocation of Rp. 51,058,734,268.85. In this way, these work items allow for evaluation, with the aim of efficiency or cost savings while remaining functional and maintaining good quality. Using the evaluation method approach, the floor base plate work item which is the sub-work of the BOC -010 elevation structure which originally used reinforcement using the conventional method was changed to using Wiremesh. After analyzing the reinforcement calculations, it was found that As w > As needed = 904.32 mm2 > 723,456 mm2. So the use of D20-150 iron bar can be replaced with M12-150 wiremesh iron. The results obtained from the results of the conversion analysis which originally used D20 – 150 iron bars, the unit price for conventional iron was Rp. 16,347.56 per kilogram to wiremesh M 12-150 unit price of Rp. 10,060.96 per kilogram. The final results show that; conventional reinforcement according to plan Rp., 16,347.56 x 122,976 = Rp. 2,010,357,646.00 while the price after changes (wiremesh) is IDR 10,060.96 x 122,976.00 = IDR. 1,237,256,616.96. The research results show that in terms of costs, by replacing conventional iron with wire mesh, savings of IDR 1,522,768,824.03 are obtained or with a savings weight of 1.19% of the total budget amount.